Management incentives and foreign ownership effect on tax avoidance with the presence of credit risk / Vidiyanna Rizal Putri ... [et al.] - Rizal Putri, Vidiyanna; Zakaria, Nor Balkish; Said, Jamaliah; Abdul Azis, Maz Ainy; Aditama Putra, Mohammad Ravi (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
Avoiding taxes, combined with government underfunding, calls into question the fairness of the tax system. While tax planning is considered legal, tax avoidance is considered illegal. Legitimate tax avoidance may involve the use of financial tools and other arrangements to obtain a tax outcome that the government did not anticipate or plan. Taxation contributes significantly to national income, so it is critical to examine the impact of management incentives and foreign ownership on tax avoidance in Indonesian conventional banks listed on the Indonesia Stock Exchange (IDX) from 2015 to 2020. The study focused on banks with foreign ownership that did not experience losses during the study period. After analysing the data with the Eviews 12 programme, it was found that foreign ownership had a negative impact on tax avoidance, although management incentives had a positive result. Furthermore, credit ratings had significant interactions with foreign ownership and management incentives for tax avoidance.